The Effects of Gender, Study Major, and Year of Study on Prospective Teachers’ Mathematical, Didactic, and Technological Knowledge - Putra, Zetra Hainul; Hermita, Neni; Yuliani, Suci; Fatmawilda, Fatmawilda (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2022)
Teachers’ mathematical, didactic, and technological knowledge has been a central issue for the last few decades. Therefore, this study investigates and compares prospective teachers’ mathematical, didactic, and technological knowledge referring to gender, year of study, and academic major. This study used an online survey through online questionnaires. The population was prospective elementary and mathematics teachers from a public university in Riau province, Indonesia. The questionnaires were distributed via WhatsApp, and LMS integrated in courses in the University. There were 195 prospective teachers participated in this study. A non- parametric statistical analysis was used to compare teachers’ knowledge based on gender, year of study, and academic major. The findings reveal that there were no significant differences of teachers’ mathematical, didactic, and technological knowledge based on gender, year of study, and academic major. Therefore, mathematics learning at university has no impact on prospective teachers’ self- evaluation of their knowledge.